Peningkatan Hasil Belajar Membaca Lancar Melalui Penggunaan Alat Peraga Kartu Huruf Dalam Pelajaran Bahasa Indonesia Pada Siswa Kelas I SDN 05 Nan Sabaris Tahun Pelajaran 2015/2016 - Erni Mayana (Indonesian Institute for Counseling, Education and Therapy (IICET), 2016)
Learning to write and read at the elementary level is the main staple for Indonesian lessons, if the student does not have the ability to read and write at the beginning of this level, it will be very difficult for any lesson. Result of preliminary observations in primary school 05 Nan Sabaris shows that there are several obstacles facing teachers in the learning process. One problem is difficult to instill the concept of reading and writing to students.The purpose of this action research are (1) to determine the extent of the use of learning resources in the form of cards letters and syllables and words can affect the ability of students in assembling and read it word for word (2) to improve the ability of students to practice reading by using cards are dealt teacher said. Data were obtained through tests and the use of the observation, the data is processed by a percentage. The results of the analysis of data obtained in the first cycle of learning success; 61.00 %, and the second cycle; amounted to 81.50%. So show no increase in student learning from the first cycle to cycle II. Thus the use of the letter cards can increase pemahamn stringing words and read to students. This is evident from the excited students verbatim via encrypted card.